Compute ∫ 1 9 9 csc − 1 ( x ) d x . Note: The above is not a reciprocal, it is arc-cosecant.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I used WA to compute the final answer. However, the way you approximated out the answer, that too with great accuracy, was superb! Loved it :)
I = ∫ 1 9 9 1 ⋅ csc − 1 x d x = x csc − 1 x ∣ ∣ ∣ ∣ 1 9 9 + ∫ 1 9 9 x x 2 − 1 x d x = 9 9 csc − 1 9 9 − 2 π + ∫ 1 9 9 x 2 − 1 1 d x = 9 9 csc − 1 9 9 − 2 π + ∫ 0 sec − 1 9 9 sec 2 θ − 1 sec θ tan θ d θ = 9 9 csc − 1 9 9 − 2 π + ∫ 0 sec − 1 9 9 sec θ d θ = 9 9 csc − 1 9 9 − 2 π + ln ( tan θ + sec θ ) ∣ ∣ ∣ ∣ 0 sec − 1 9 9 = 9 9 csc − 1 9 9 − 2 π + ln ( 7 0 2 + 9 9 ) − ln ( 0 + 1 ) = 9 9 csc − 1 9 9 − 2 π + ln ( 7 0 2 + 9 9 ) ≈ 4 . 7 1 7 By integration by parts Note that d x d csc − 1 x = − x x 2 − 1 1 Let x = sec θ ⟹ d x = sec θ tan θ d θ
Problem Loading...
Note Loading...
Set Loading...
First, let's take the indefinite integral using integration by parts.
I = ∫ csc − 1 ( x ) d x
Let u = csc − 1 ( x ) , and d v = d x , so d u = − x x 2 − 1 d x (for x > 0 ), and v = x . Then, I = u v − ∫ v d u = x csc − 1 ( x ) + ∫ x 2 − 1 d x
Now if we make the trig. substitution x = sec θ ⇒ d x = sec θ tan θ ,
→ ∫ x 2 − 1 d x = ∫ sec θ d θ = ln ( sec θ + tan θ ) = ln ( sec θ + sec 2 θ − 1 ) = ln ( x + x 2 − 1 )
(for x > 0 , ignoring the constant of integration)
So we have I = x csc − 1 ( x ) + ln ( x + x 2 − 1 )
Now, our definite integral is I ( 9 9 ) − I ( 1 ) .
I ( 1 ) = csc − 1 ( 1 ) = sin − 1 ( 1 ) = 2 π . We can approximate 2 π as 1 . 5 7 .
Here's the fun part, approximating our way to
I ( 9 9 ) = 9 9 csc − 1 ( 9 9 ) + ln ( 9 9 + 9 9 2 − 1 )
For the first term, since csc − 1 ( x ) = sin − 1 ( x 1 ) , we want 9 9 sin − 1 ( 9 9 1 ) .
Now we can use the small-angle approximation sin x ≈ x (since 9 9 1 is close enough to 0 ), so that sin − 1 ( x 1 ) ≈ x 1 . Then 9 9 sin − 1 ( 9 9 1 ) = 9 9 csc − 1 ( 9 9 ) is pretty close to 1 .
For the second term, after working 9 9 2 out, we want to find ln ( 9 9 + 7 0 2 ) .
Approximating 2 as 1 . 4 1 4 , 7 0 × 1 . 4 1 4 = 9 8 . 9 8 .
In order to find ln ( 9 9 + 9 8 . 9 8 ) = ln ( 1 9 7 . 9 8 ) , we can split this into
ln ( 1 . 9 7 9 8 ) + ln ( 1 0 2 ) = ln ( 1 . 9 7 9 8 ) + 2 ln ( 1 0 ) .
I got pretty lucky like Richard Feynman this time, because I don't know by heart the natural logs of anything besides 2 and 1 0 , and I think I even learned ln 1 0 from Feynman's Surely You're Joking, Mr. Feynman! .
Anyway, we can approximate ln 1 . 9 7 9 8 as ln 2 which is approximately 0 . 6 9 , and we can approximate ln 1 0 as 2 . 3 .
Notice that this method of taking ln ( x ⋅ 1 0 n ) = ln x + n ln 1 0 allows us to decently approximate the natural logs of really large or small numbers, as long as you know the nat. logs of the first 10 integers; pretty cool!
Back to the problem, we then have that ln ( 1 9 7 . 9 8 ) ≈ ln 2 + 2 ln 1 0 ≈ 0 . 6 9 + 4 . 6 = 5 . 2 9 .
So we have I ( 9 9 ) ≈ 1 + 5 . 2 9 = 6 . 2 9 .
Finally, ∫ 1 9 9 csc − 1 ( x ) d x = I ( 9 9 ) − I ( 1 ) ≈ 6 . 2 9 − 1 . 5 7 = 4 . 7 2 .